The Effect Of Date Palm Extract On Hemoglobin Levels In Third Trimester Pregnant Women At UPT Puskesmas Sekincau, West Lampung Regency, 2024 - Wiwit Yuliana; Yuni Sulistiawati; Beniqna Maharani Besmaya; Yona Desni Sagita (Jurnal EduHealth, 2024)
Anemia in pregnant women is a classic problem that can never be treated, has a serious impact on the mother and baby, and if not treated immediately, it can prolong the latent phase, the active phase, and cause primary post-partum bleeding. In the fetus it can cause IUGR, prematurity, LBW. Data on pregnant women at the Sekincau Community Health Center in 2023 was 586 and 24.7% had anemia in pregnancy. One intervention that can be done is consuming foods high in iron and vitamin C, namely date palm juice. The aim of the research was to determine the effect of giving date palm juice on the hemoglobin levels of TM III pregnant women. Quantitative research type, Quasi-experimental research design with a two group pretest-posttest design approach. The population was 77, the sample was 30, divided into 2 groups, 15 intervntion groups and 15 control groups using purposive sampling techniques and simple random sampling techniques. The object of the research was hemoglobin levels. The research subjects were pregnant women in the third trimester with anemia. The research was conducted in July-August 2024. Data collection used observation sheets, univariate and bivariate data analysis (Independent t-test). The results of the study showed that the average hemoglobin level before being given date juice and Fe (intervention group) was 10.2 gr/dl and after the intervention was 11.4 gr/dl. Meanwhile, the average hemoglobin level before being given Fe alone (control group) was 10.0 gr/dl and after it was 10.3 gr/dl. There was an effect of giving date palm juice on the hemoglobin levels of TM III pregnant women (p-value 0.000 < α = 0.05). Advice for pregnant women: Date palm juice is a complement to increasing Hb levels in pregnant women